Association of Monocarboxylate Transporter-1 (MCT1) A1470T Polymorphism (rs1049434) with Forward Football Player Status. - Massidda, Myosotis; Mendez-Villanueva, Alberto; Ginevičienė, Valentina; Proia, Patrizia; Drozdovska, Svitlana B.; Dosenko, Victor; Scorcu, Marco; Stula, Aleksander; Sawczuk, Marek; Cięszczyk, Paweł; Calò, Carla Maria (International Journal of Sports Medicine, 2018)
The aim of this study was to investigate the association between the MCT1 (monocarboxylate transporter 1) A1470T polymorphism and positional roles in a large cohort of professional football players from five different countries. We compared genotype distributions of the MCT1 A1470T polymorphism between football players (n=694) and non-athlete controls (n=781) from Italy, Poland, Lithuania, Ukraine and Malta, and we analyzed the MCT1 genotype distributions with respect to the players’ positions in the field (e. g. forwards, midfielders, defenders and goalkeepers). Genomic DNA was extracted from either buccal epithelium or peripheral blood using a standard protocol. In the pooled cohort of Italian, Polish, Lithuanian and Ukrainian football players, forwards (n=148) were more likely than controls (n=781) to possess the A allele (χ2=7.067, p=0.029, FDR q value 0.116), with a greater likelihood of having the AA genotype compared with the TT genotype (OR=1.97; C.I.=1.07-3.64; p=0.021, FDR q value 0.086). The MCT1 AA genotype was significantly more frequent in forwards then in controls. Further studies are needed to confirm these findings in other professional football player cohorts.
Keywords: genetic differences; lactate; monocarboxylate transporter-1; repeated sprint ability; soccer